Challenges in Mechanics of Time Dependent Materials, Volume 2 Proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics (Conference Proceedings of the Society for Experimental Mechanics Series,, 2018)
Challenges in Mechanics of Time-Dependent Materials, Volume 2 of the Proceedings of the 2017 SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the second volume of nine from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers in the following general technical research areas: Characterization Across Length Scales Extreme Environments & Environmental Effects Viscoelasticity Structure Function Performance Polymer Viscoplasticity Metallic Materials Fracture/Fatigue/Damage Composites Soft Materials.